깊이에 높은 응력 크기를 갖는 유리-계 물품 - WILANTEWICZ TREVOR EDWARD; SCHNEIDER VITOR MARINO (2020)
유리-계 물품은, 제1 표면과 제2 표면 사이에 중심 및 두께 (t)를 한정하는, 제1 표면 및 상기 제1 표면에 대향하는 제2 표면을 가지며, 상기 유리-계 물품은, LiO, 이온-교환된 칼륨 및 이온-교환된 나트륨을 함유한다. 상기 유리-계 물품은, 상기 제1 표면 (또는 제1 표면 아래의 지점)으로부터 0.001·t 내지 0.1·t 범위의 정점으로 연장되는 험프 응력 영역을 포함하는, 응력 프로파일을 갖는다. 상기 정점에서 압축 응력은 25 내지 750 MPa이다. 상기 험프 영역은, 증가하는 응력의 구역 및 감소하는 응력의 구역을 포함한다. 압축의 깊이는 0.1·t 내지 0.25·t이다. 인장 응력 영역은 압축의 깊이로부터 최대 인장 응력까지 연장된다. Glass-based articles have a first surface and a second surface opposing the first surface defining a thickness (t) and a center between the first surface and the second surface, the glass-based article containing Li2O, ion-exchanged potassium and ion-exchanged sodium. The glass-based article has a stress profile including a hump stress region extending from the first surface (or a point below the first surface) to an apex in a range of 0.001·t and 0.1·t. Compressive stress at the apex is from 25 to 750 MPa. The hump region comprises an area of increasing stress and an area of decreasing stress. Depth of compression is from 0.1·t to 0.25·t. A tensile stress region extends from the depth of compression to a maximum tensile stress.